Introducing communication research : paths of inquiry - Treadwell, D. F. (Donald Francis); Davis, Andrea, (Andrea M.) (Thousand Oaks: Sage, 2020)
"Introducing Communication Research: Paths of Inquiry, Fourth Edition demystifies the theories and applications of communication research through its focus on methods in practice. Offering an overview of the research process with a focus on examples of research in real-world settings, this text introduces both quantitative and qualitative methods."--
Includes bibliographical references and Index.
Keywords: Communication -- Research -- Methodology